2020
DOI: 10.1111/nmo.14060
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic yield of adding solid food swallows during high‐resolution manometry in esophageal motility disorders

Abstract: High-resolution manometry (HRM) is a key diagnostic method to evaluate esophageal motility disorders in patients with dysphagia when endoscopic and radiologic techniques do not clarify the cause of symptoms. Impaired esophageal motility may be detected while drinking or eating. Current evaluation with HRM is usually performed only with single water swallows (SWS). However, liquid may not challenge esophageal function adequately or reproduce symptoms. This may be because small volume water swallows are

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Provocative testing is easy, cheap, and confirmed to be useful for defining other minor and major motility disorders. 2,3,8,24,28,29 Our study showed that overall, 44.9% of patients demonstrated different manometric features during the SM, compared to the standard SWS. RDC has been shown to be an effective measure of obstruction in patients with achalasia in several studies.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Provocative testing is easy, cheap, and confirmed to be useful for defining other minor and major motility disorders. 2,3,8,24,28,29 Our study showed that overall, 44.9% of patients demonstrated different manometric features during the SM, compared to the standard SWS. RDC has been shown to be an effective measure of obstruction in patients with achalasia in several studies.…”
Section: Discussionmentioning
confidence: 60%
“…On the other hand, during the SM, although 70 patients had SWS diagnosis reaffirmed, in 57 (44.9%) the diagnosis changed to a different phenotype of achalasia. Studies have repeatedly demonstrated that the inclusion of solids during HRM has the ability to change diagnosis, and therefore improve the diagnostic yield 2,11,28,29 . Ang et al described how achalasia subtype changed in five patients after solids were introduced with spasm and hypercontractile patterns becoming apparent 2 …”
Section: Discussionmentioning
confidence: 99%
“…The upright posture better replicates normal eating and improves detection of motility disorders (200) and hiatal herniation (244). If findings are equivocal, solid foods may be administered (245,246) or post-prandial monitoring ( 247) is performed to improve diagnostic yield.…”
Section: Methodsmentioning
confidence: 99%
“…The previous Chicago classification version 3 (CCv3.0) included only 10 mL water swallows in the supine position [37]. However, many studies suggested that adjunctive tests could improve the diagnostic yield of HRM for the detection of motility disorders and for better defining the clinical relevance of these findings [38][39][40][41][42]. Furthermore, to ease the implementation of solid swallows in routine clinical practice, Hollenstein et al performed a development and validation study that aimed to define normal values of esophageal metrics for solid swallows.…”
Section: High-resolution Manometry and The Chicago Classification Version 40mentioning
confidence: 99%